The American musical and the performance of personal identity - Knapp, Raymond (Princeton University Press, 2009)
The American musical has long provided an important vehicle through which writers, performers, and audiences reimagine who they are and how they might best interact with the world around them. Musicals are especially good at this because they provide not only an opportunity for us to enact dramatic versions of alternative identities, but also the material for performing such alternatives in the real world, through songs and the characters and attitudes those songs project. This book addresses a variety of specific themes in musicals that serve this general function: fairy tale and fantasy, idealism and inspiration, gender and sexuality, and relationships, among others. It also considers three overlapping genres that are central, in quite different ways, to the projection of personal identity: operetta, movie musicals, and operatic musicals. --From publisher's description.